2009
DOI: 10.1179/174313209x380964
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of endovascular coil embolization for cerebral aneurysms using three-dimensional time-of-flight magnetic resonance angiography

Abstract: Objectives: As endovascular treatment becomes more prevalent, aneurysm recurrence from neck remnants, recanalization, incomplete obliteration and bleeding remain major concerns. In the current analysis, we attempted to identify factors related to disease progression and clinical outcome in patients treated with coil embolization. Methods: This study included 58 patients who underwent endovascular coil embolization for treatment of intracranial aneurysm. The result of embolization was evaluated with threedimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This complication is known in the treatment of large aneurysms treated with coils only without a flow diverter [5,7]. The exact mechanism is not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…This complication is known in the treatment of large aneurysms treated with coils only without a flow diverter [5,7]. The exact mechanism is not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…All 8.6% cases of PAVO in one series were associated with aneurysm recanalisation2 of which at least three improved with re-treatment of the aneurysm 3. However, Su et al report no statistically significant correlation between PAVO and aneurysm recanalisation, but describe three cases, at least two of which improved with re-treatment of the aneurysm 4…”
Section: Discussionmentioning
confidence: 91%
“…The majority of the case reports describe symptoms, whereas the three case series with routine postembolisation MRI imaging, 0/455 and 1/104 are symptomatic; the third is not mentioned 2. The asymptomatic cases were not treated and three cases with minor self-limiting symptoms including hypoesthesia,18 intermittent paraesthesia14 and hypersomnolence17 were not treated.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Kwee study, further reports have shown TOF‐MRA to be an excellent imaging modality for follow‐up of coiled aneurysms . Of those studies that looked specifically at whether MRA can replace DSA as the primary imaging modality for follow‐up of intracranial aneurysm coiling, only one concluded that DSA could not be replaced .…”
Section: Discussionmentioning
confidence: 99%
“…Since the Kwee study, further reports have shown TOF-MRA to be an excellent imaging modality for follow-up of coiled aneurysms. 14,16,17,[21][22][23] Of those studies that looked specifically at whether MRA can replace DSA as the primary imaging modality for follow-up of intracranial aneurysm coiling, 14,16,17,24 only one concluded that DSA could not be replaced. 24 Deutschmann et al, 25 while investigating the effect of aneurysm size and location on diagnostic accuracy of TOF-MRA, found that TOF-MRA was worse than DSA for detection of recurrence if the aneurysm was <3 mm.…”
Section: Discussionmentioning
confidence: 99%